Monosodium Urate Crystals Activate the Inflammasome in Primary Progressive Multiple Sclerosis - Piancone, Federica; Saresella, Marina; Marventano, Ivana; La Rosa, Francesca; Santangelo, Maria Antonia; Caputo, Domenico; Mendozzi, Laura; Rovaris, Marco; Clerici, Mario (Frontiers in Immunology, 2018)
Inflammasome-driven inflammation is postulated to play a role in Multiple Sclerosis (MS), but there is no direct evidence that the nod-like receptor protein 3 (NLRP3) inflammasome is involved in MS pathogenesis. Uric acid was shown to be one of the ‘danger’ signals involved in the activation of NLRP3 inflammasome; notably, the concentration of uric acid is increased in the serum and in the cerebro-spinal fluid (CSF) of MS individuals. To better investigate the role of the NLRP3 inflammasome in MS-associated inflammation we primed with LPS and stimulated with Monosodium Urate Crystals (MSU) PBMCs of 41 MS patients with different disease phenotypes. Eleven individuals with primary progressive MS (PPMS), 10 individuals with stable relapsing-remitting MS (SMS), 10 individuals with acute relapsing- remitting MS (AMS), 10 individuals with benign MS (BMS) were analyzed; 10 healthy controls (HC) were enrolled as well in the study. The expression of the NLRP3, apoptosis-associated speck-like protein containing CARD (ASC), caspase-1, caspase-8, IL-1β and IL-18 inflammasome genes was evaluated by RT-PCR. NLRP3 and ASC-speck protein expression was analyzed by FlowSight AMNIS, whereas production of the pro-inflammatory cytokines IL-1β and IL-18 and of caspase-1 and caspase-8 was measured by ELISA in supernatants. Results showed that uric acid serum concentration was significantly increased in PPMS; in these and in AMS patients, mRNA for NLRP3, ASC and IL-18 was up regulated as well, but caspase-8 mRNA was up regulated only in PPMS. Expression of NLRP3 and ASC-speck protein was significantly increased in PPMS, SMS and AMS patients, but IL-18 and caspase-8 production was significantly increased only in PPMS, in whom a direct correlation between hyperuricemia and caspase-8 was detected. The NLRP3/caspase-8 inflammasome pathway is activated in PPMS, possibly as a consequence of hyperuricemia. Therapeutic strategies reducing NLRP3 activation and/or lowering hyperuricemia could be useful in the therapy of PPMS.